Factors Influencing Intimate Partner Violence: Experience of Victims and Survivors Among Women and Men Aged 15-49 Years in Nangabo Sub-county, Wakiso District - Mark Owen Onen (Uganda Christian University, 2024)
Background Intimate Partner Violence (IPV) is not only a serious public health problem but also concerns the violation of human rights in Uganda as it affects individuals across various socioeconomic, religious and cultural divides [8],[-10]. This research explores the lived experiences of victims-cum- survivors: (1) often unnamed women, one case study being a woman from Nangabo sub-county Wakiso District. The main focus of the sessions will be on IPV, specifically physical and psychological violence which are experienced more by women; according to Uganda Demographic and Health Survey (2016) 51% of ever-married young adult men aged 15–49 have perpetrated sexual or/and non-sexual intimate partner violence against their female partners compared with at least one in two decennium. Poverty, low education levels substance abuse and iniquitous gender norms are the key drivers of IPV victimization in Uganda. The study objectives are to evaluate the determinants of IPV, examine community norms and behaviors related to IPV and assess impact of increased rates in local areas. This research utilizes qualitative methods, that center lived experiences to understand the structural and social underpinnings of IPV. The results will facilitate the design of personalized interventions, policy-making and further advocacy actions that strive to minimize IPV as well as improve victim care in Nangabo sub-county. Pertinent to the literature, this study demonstrated a prevalence of both physical and sexual IPV among women in Karachi that deserves further attention; while limited by sample size and generalization, serves as an important pilot project on how addressing violence against woman should be urgently targeted through community-based multi-stakeholder collaboration. Before we close our manuscript but you can add some spirit motivated your advocacy for intervention at large scale/policy level.